(untitled) (Лучшие интеллектуальные исследования, 2025)
This thesis explores the interrelationship between play, motivation, and skill development in second or foreign language learning. It emphasizes the pedagogical value of integrating playful learning strategies and motivational techniques in classroom contexts to enhance language proficiency. Drawing on recent theoretical and empirical research, the study investigates how games, interactive tasks, and positive reinforcement contribute to strengthening core language skills—listening, speaking, reading, and writing. The discussion includes live classroom examples and analyses the psychological and cognitive mechanisms that underpin playful and motivational language learning. The paper concludes that incorporating play and motivation significantly fosters language acquisition and learner autonomy, especially in young and adolescent learners.